Preventive vaccines for COVID-19. An expectant reality - Ana María Ramos Cedeño; Yeny Dueñas Pérez; Alicia del Rosario Ramírez Pérez (Medisur)
Throughout the history of humanity, the full development of vaccines for the prevention of diseases that constitute pandemics is evident. The population of this century suffers the vicissitudes of the new coronavirus, and exposes an ongoing global health emergency, caused by the severe acute respiratory syndrome coronavirus 2. The high transmissibility and mortality, with the involvement of almost all the countries on the planet, without distinction between economic systems, it has unleashed a race to obtain a preventive vaccine that could stop the tragedy. However, its introduction into medical practice is a path that involves specific procedures and compliance with ethical standards. Accordingly, some considerations are exposed in this work.